THE BENEFITS OF PHYSIOTHERAPY IN THE TREATMENT OF POSTPARTUM DIASTASIS - Leticia Da Silva Ferreira, Bruna (Health and Society, 2023)
The diastasis of the rectus abdominis muscle (ARMD) is a physiological change that occurs in the female body due to pregnancy, hormonal changes, mechanical stress on the abdominal wall by fetal growth and displacement of abdominal organs. Physiotherapy plays a very important role, promoting a stimulation mainly of the abdominal and pelvic muscles to improve muscle tone.